Intra-aortic balloon pumping: seven years' experience. Issue 11 (November 1985) - Vigneswaran, W T; Reece, I J; Davidson, K G
Abstract : The indications for intra-aortic balloon pumping vary widely from country to country and from one cardiac surgical unit to another. Its use in Glasgow from 1976 to 1983 in 63 patients has been reviewed. Six of the patients (9.5%) had the intra-aortic balloon inserted before cardiac surgery, 43 (68.2%) at the time of surgery, and 14 (22.2%) in the postoperative period. Of the 63 patients, 11 could not be weaned from cardiopulmonary bypass despite intra-aortic balloon pumping, and died in the operating room. A further 35 patients had intra-aortic balloon pumping but died in the immediate postoperative period. Seventeen patients (27%) survived from six weeks to 3.3 years after receiving the support of intra-aortic balloon pumping. There was major morbidity in 11 patients (17%), all of whom developed degrees of ischaemia due to ileofemoral arterial obstruction in the leg in which the balloon was inserted. The conservative use of the method in this centre is reflected in the high mortality of these patients.